Evaluation of temperature increase during in-office bleaching - Rafael Francisco Lia MONDELLI; Ana Flávia SOARES; Eugenio Gabriel Kegler PANGRAZIO; Linda WANG; Sergio Kiyoshi ISHIKIRIAMA; Juliana Fraga Soares BOMBONATTI (University of São Paulo, 2016)
ABSTRACT The use of light sources in the bleaching process reduces the time required and promotes satisfactory results. However, these light sources can cause an increase in the pulp temperature. Objective The purpose of the present study was to measure the increase in intrapulpal temperature induced by different light-activated bleaching procedures with and without the use of a bleaching gel. Material and Methods A human maxillary central incisor was sectioned 2 mm below the cementoenamel junction. A K-type thermocouple probe was introduced into the pulp chamber. A 35% hydrogen peroxide bleaching gel was applied to the vestibular tooth surface. The light units used were a conventional halogen, a hybrid light (only LED and LED/Laser), a high intensity LED, and a green LED light. Temperature increase values were compared by two-way ANOVA and Tukey´s tests (p<0.05). Results There were statistically significant differences in temperature increases between the different light sources used and between the same light sources with and without the use of a bleaching gel. The presence of a bleaching gel generated an increase in intra-pulpal temperature in groups activated with halogen light, hybrid light, and high intensity LED. Compared to the other light sources, the conventional halogen lamp applied over the bleaching gel induced a signiﬁcant increase in temperature (3.83±0.41°C). The green LED unit with and without gel application did not produce any significant intrapulpal temperature variations. Conclusion In the present study, the conventional halogen lamp caused the highest increase in intrapulpal temperature, and the green LED caused the least. There was an increase in temperature with all lights tested and the maximum temperature remained below the critical level (5.5°C). The addition of a bleaching gel led to a higher increase in intrapulpal temperatures.